Analisis Pengelolaan Bank Sampah Oleh Badan Usaha Milik Desa Di Desa Jegulo Kecamatan Soko Kabupaten Tuban - Luluk Ayu Widyantika; Suprapto Suprapto; Fatkur Mu'in; Susilowati Rahayu (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2022)
Village Development is essentially the basis of national development, one of the programs that has been implemented by the government for village development, namely through Village Owned Enterprises. One of the villages that already has a Village-Owned Enterprise is Jegulo Village, a program that has been implemented for the development of the Jegulo Village, namely through the Waste Bank. The purpose of this study was to determine the development of waste bank management by Village Owned Enterprises. The method used is descriptive qualitative. The sampling technique used is purposive and is snowball sampling. Research subjects were seven people. The results of this study point out that the Srikandi Berseri waste bank, which is managed by the Jegulo Village-Owned Enterprise, in the development of waste management, processes inorganic waste by recycling it into various crafts such as bags, containers of mineral water, brooches and others. However, there are several obstacles in the development of waste bank management, namely the level of knowledge that is still low and the mindset that is still not open.